Terrorism: world under siege - Ghosh, S. K. (New Delhi, 1995)
The book highlights terrorist activities in their various manifestations, such as, kidnppings, abductions, hijackings, hostage, seizures, extortions, assassinations and bombing around the world and more specifically in India.
Keywords: Terrorism-India